Chemodivergent Spirocyclization of 2‐Sec‐Aminobenzilidene Imidazolones: Lewis Versus Brønsted Acids Catalysis. Issue 9 (8th April 2022) - Ivanov, Dmitrii S.; Zaitseva, Elvira R.; Smirnov, Alexander Yu.; Rustamova, Dina A.; Mikhaylov, Andrey A.; Sycheva, Maria A.; Gluschenko, Darya A.; Baleeva, Nadezhda S.; Baranov, Mikhail S.
Abstract: Benzylidene imidazolones with ortho‐ secondary aminogroup undergo acid‐promoted chemodivergent spirocyclization. Strong Lewis acids provide access to spirocyclic tetrahydroquinolines via [1, 5]‐hydride shift triggered cyclization despite of the presence of free secondary amino group. Brønsted acids promote unprecedented intramolecular umpolung hydroamination reaction with the formation of spirocyclic indolines. Each of the processes proceeds with exclusive atom‐economy. Abstract :